ORCID Adoption by the LIS Faculty Community of India: A Case Study - Jain, Sanjeev Kumar; Makwana, Jignesh; Navas R, Kaja Bantha (DESIDOC Journal of Library & Information Technology, 2023)
The study aims to evaluate the utilisation of ORCID (Open Researcher and Contributor identifier) among LIS faculty members at UCG-approved Indian universities. An online survey was conducted to collect data from a representative group of 369 faculty members. LIS field who are associated with Indian Universities and actively involved in teaching and research activities. A simple random sampling procedure was used in the study to collect samples from respondents. Total 164 completed responses were received, with a response rate of 44.44 %. The results suggest that LIS faculty members had high awareness of ORCID. ORCID is a widely used system by LIS faculty members specially used to find and share information about research articles. The gender-wise awareness, ORCID Holders and the types of recommendations, ORCID Holder usage time examined. This study aims to provide a comprehensive analysis exploring the ORCID adoption among LIS faculty members in India and addresses multiple objectives.